Research in the designing and engeneering of sublimation drying systems at low productivity level with refrigeration cycles in the sublimation chamber - Nguyen, Tấn Dũng; Trinh, Văn Dũng; Tran, Đức Ba (Journal of Technical Education Science, 2009)
A most modern method of processing and preserving food in the world today is the sublimation drying method. It dries foods at a temperature range of -45oC to 40oC without changing the substances’ characteristics: the proteins are not denatured, the lipids not oxidized, the vitamines and natural pigments and smells not destroyed, etc. It is for this reason that it is indispensable to do research in the designing and engeneering of sublimation drying systems to use in Vietnam in order not to be dependent on foreign technologies